2017
DOI: 10.1128/mbio.00438-17
|View full text |Cite
|
Sign up to set email alerts
|

Preprinting Microbiology

Abstract: The field of microbiology has experienced significant growth due to transformative advances in technology and the influx of scientists driven by a curiosity to understand how microbes sustain myriad biochemical processes that maintain Earth. With this explosion in scientific output, a significant bottleneck has been the ability to rapidly disseminate new knowledge to peers and the public. Preprints have emerged as a tool that a growing number of microbiologists are using to overcome this bottleneck. Posting pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…The distribution of time to publication is similar to the results from Larivière et al (2014) showing preprints on arXiv were most frequently published within a year of being posted there, and to a later study examining bioRxiv preprints that found “the probability of publication in the peer-reviewed literature was 48% within 12 months” (Serghiou and Ioannidis 2018). Another study published in spring 2017 found that 33.6 percent of preprints from 2015 and earlier had been published (Schloss 2017); our data through November 2018 show that 68.2 percent of preprints from 2015 and earlier have been published. Multiple studies have examined the interval between submission and publication at individual journals (e.g.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The distribution of time to publication is similar to the results from Larivière et al (2014) showing preprints on arXiv were most frequently published within a year of being posted there, and to a later study examining bioRxiv preprints that found “the probability of publication in the peer-reviewed literature was 48% within 12 months” (Serghiou and Ioannidis 2018). Another study published in spring 2017 found that 33.6 percent of preprints from 2015 and earlier had been published (Schloss 2017); our data through November 2018 show that 68.2 percent of preprints from 2015 and earlier have been published. Multiple studies have examined the interval between submission and publication at individual journals (e.g.…”
Section: Discussionsupporting
confidence: 40%
“…We know bioRxiv is the largest of the biology-focused preprint servers: Of the eight websites indexed by PrePubMed (http://www.prepubmed.org), bioRxiv now consistently posts more than three times as many articles per month as the other seven combined (Anaya 2018). Sporadic updates from bioRxiv leaders show a chain of record-breaking months for submission numbers (Sever 2018), and analyses have examined metrics such as total downloads (Serghiou and Ioannidis 2018) and publication rate (Schloss 2017). But long-term questions remain open: Which fields have posted the most preprints, and which collections are growing most quickly?…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the biological sciences have experienced the phenomenon of the preprint movement ( 3 5 ). Although the circulation of unpublished papers has long been used by other disciplines, the notion of depositing unpublished papers in preprint servers that are available to all free of charge is new to biology.…”
Section: Editorialmentioning
confidence: 99%
“…These frameworks have been applied to research on microbially-mediated nitrogen and carbon cycling but have not been applied to study microbially-mediated P cycling in natural and agricultural settings. As researchers establish studies to explore microbial P cycling in new habitats, they can refer to previous work for guidance on microbial-scale ecological theories (Choudoir et al, 2017;Prosser et al, 2007), statistical approaches and considerations (Bernhardt et al, 2017;Bier et al, 2015;Buttigieg & Ramette, 2014;Rocca et al, 2015;Schimel & Gulledge, 1998;Willis, 2016;Willis et al, 2017), method overviews (Ekblom & Wolf, 2014;Pallen, 2016;Schloss, 2020;Zimmerman et al, 2014), bioinformatics (Cock et al, 2009;Loman & Watson, 2013;Shade & Teal, 2015;Wilson et al, 2016), reproducible research (da Veiga Leprovost et al, 2014;Perez-Riverol et al, 2016;Schloss, 2017;Shade & Teal, 2015;Wilson et al, 2016), and modelling (Graham et al, 2014(Graham et al, , 2016Manzoni et al, 2014;Reed et al, 2014;Todd-Brown et al, 2012;Wieder et al, 2013).…”
Section: Promising Diagnostic Tools and Research Applications For Agricmentioning
confidence: 99%